2003
DOI: 10.1128/jvi.77.18.9831-9844.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Disease and Pulmonary Eosinophilia Associated with Formalin-Inactivated Respiratory Syncytial Virus Vaccination Are Linked to G Glycoprotein CX3C-CX3CR1 Interaction and Expression of Substance P

Abstract: Vaccination with formalin-inactivated respiratory syncytial virus (FI-RSV) vaccine or RSV G glycoprotein results in enhanced pulmonary disease after live RSV infection. Enhanced pulmonary disease is characterized by pulmonary eosinophilia and is associated with a substantial inflammatory response. We show that the absence of the G glycoprotein or G glycoprotein CX3C motif during FI-RSV vaccination or RSV challenge of FI-RSV-vaccinated mice, or treatment with anti-substance P or anti-CX3CR1 antibodies, reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
102
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 78 publications
3
102
0
3
Order By: Relevance
“…Enhanced disease and pulmonary eosinophilia associated with FI-HRSV were reported in the 1960s, when a disease-exacerbating FI vaccine was administered to infants and children in the United States (9,17,35,61), and were also demonstrated in mice (12,20,25,28,44). In the present study, the percentage of eosinophils was 34% in the lungs of mice vaccinated with FI-BRSV, while this was reduced to 1% when CpG ODN was added.…”
Section: Discussionmentioning
confidence: 60%
“…Enhanced disease and pulmonary eosinophilia associated with FI-HRSV were reported in the 1960s, when a disease-exacerbating FI vaccine was administered to infants and children in the United States (9,17,35,61), and were also demonstrated in mice (12,20,25,28,44). In the present study, the percentage of eosinophils was 34% in the lungs of mice vaccinated with FI-BRSV, while this was reduced to 1% when CpG ODN was added.…”
Section: Discussionmentioning
confidence: 60%
“…A similar enhancement is also seen when mice are sensitized with the RSV-G glycoprotein [16] or vaccinia virus expressing the secreted form of the RSV G glycoprotein [17]. The severe disease that followed challenge with RSV was associated with elevated levels of IL-4, -5, -13 and eotaxin [18].…”
mentioning
confidence: 65%
“…Early trials with formalin-inactivated respiratory syncytial virus (FI-RSV) found that the vaccines not only did not protect children against RSV but also appeared to increase the attack rate and clinical severity of later natural infection with RSV [13][14][15], possibly contributing to some deaths [16]. It has been suggested that exacerbation of disease after RSV vaccination and, possibly also in the presence of maternal antibodies, was also due to ADE mechanisms during later natural infections with RSV [13].…”
mentioning
confidence: 99%
“…Through this motif, the RSV G protein binds to the fractalkine receptor, CX3CR1, and this interaction facilitates virus infection and modulates leukocyte chemotaxis (Tripp et al, 2001), including adversely affecting CX3CR1 + T cell responses (Harcourt et al, 2006). Studies have shown that antibodies that block G protein CX3C-CX3CR1 interaction protect against some of the G protein-associated enhanced inflammation observed after RSV infection (Haynes et al, 2003). In addition, anti-RSV G protein antibody responses after natural infection or vaccination with live-attenuated RSV vaccine in young children are associated with the inhibition of G protein-mediated human leukocyte migration and G protein CX3C-CX3CR1 interaction (Harcourt et al, 2004).…”
mentioning
confidence: 99%